Using Multimedia Instruction and Performance Feedback to Improve Preservice Teachers' Vocabulary Instruction. (August 2019) - Peeples, Katherine N.; Hirsch, Shanna Eisner; Gardner, Stephanie J.; Keeley, Randa G.; Sherrow, Breanna L.; McKenzie, Jennifer M.; Randall, Kristina N.; Romig, John Elwood; Kennedy, Michael J.
High-quality, effective vocabulary instruction is essential for supporting all students' academic success, and it is particularly important for students with disabilities. Teacher preparation programs are faced with the challenge of not only training preservice teachers to provide effective vocabulary instruction across grades and content areas, but also to prepare them to teach students with disabilities. This randomized control trial included 200 preservice teachers. We tested the effects that a combination of multimedia instruction and performance feedback on evidence-based practices for effective vocabulary instruction had on participants' knowledge and application of those practices. Compared with participants who received traditional lecture and text-based instruction and subjective feedback, we found that the group that received multimedia instruction and performance feedback implemented more of the practices, more frequently and for a longer duration. Implications for research and teacher preparation are discussed.